Requirements for an electronic handover system for interprofessional collaboration between psychotherapists and occupational health professionals - a qualitative study - Fiona Kohl; Peter Angerer; Lisa Guthardt; Jeannette Weber (BMC, 2022)
Abstract Background An electronic handover system provides a potential way to bridge the interface between psychotherapy and occupational health. This qualitative study therefore aimed assessing (1) content-related and (2) functional requirements that psychotherapists and occupational health professionals expect from an electronic handover system to exchange relevant information about their patients with common mental disorders. Methods Five focus groups with psychotherapists and occupational health professionals (occupational physicians and members of company integration management) were conducted via video conference using an interview guide. The focus groups were transcribed and content-analysed using MAXQDA. Results With regard to content-related requirements, information that serve to assess employee's ability to work was described as particularly relevant by occupational physicians and members of company integration management (e.g. restrictions in certain work areas or ability to work under time pressure). Psychotherapists indicated that information about the employee's working conditions is particularly relevant. This includes description of work tasks or conflicts at the workplace. Concerning functional requirements, all professional groups attached importance to data security and functions to improve communication and collaboration (e.g. the use of standardised handover forms). Conclusion This study provides insight into the desired content-related and functional requirements by psychotherapists, occupational physicians and members of company integration management for an electronic handover system. However, the theoretical and practical development of such a system requires several additional steps, such as the involvement of further relevant stakeholders (e.g. patients, software developers).